Implikasi Putusan Mahkamah Konstitusi Nomor 22-24/PUU- VI/2008 terhadap Kebijakan Affirmative Action Keterwakilan Perempuan di DPRD Provinsi dan kabupaten/kota se-Daerah Istimewa Yogyakarta - Pusat Studi Hukum Konstitusi FH UII (The Constitutional Court of the Republic of Indonesia, 2010)
The research concluded, first, The Constitutional Court decision number 22-24/PUU-VI/2008 give the positive implications of affirmative action policy of women representation in the provincial parliament and regency/town in Yogyakarta, because every legislative candidates have equal opportunity to fight to obtain a majority vote in 2009 legislative elections. Second, when Law no. 10 year 2008 still use a list of serial numbers, women’s position in the list of candidates a majority in the lowest sequence number, the result difficult for female candidates to gain seats as if his voice does not reach the number of automatic splitter sounds will be given to the serial number on it, but with a majority vote model , greater opportunities for female candidates was elected. Third, women representation in the provincial parliament Daerah Istimewa Yogyakarta (DIY) increased when compared with the results of the election of 2004, from 9 seats in 2009 elections to 12 seats, so there is an increase of 33%. in Gunung Kidul district legislature also increased the number of seats of women when compared with the acquisition of seats in the elections of 2004, from a seat in the 2009 election to 6 seats, so there is 500%. Sleman district legislature in the 2004 elections the number of women seats and as many as 6 seats in the 2009 election to 8 seats. So the increase of about 33%. in Yogyakarta city parliament also increased the number of seats in 2004 elections from 5 to 6 seats in 2009 elections. Thus, there is an increase of 20%. Kulonprogo parliament,the seats for women who gained in the 2004 elections and are 4 seats in the 2009 election into 4 seats so that there is an increase of 25%, and in Bantul Regency 2004 election results there are only 5 seats for women, in the 2009 election to 6 people or up 20%. Fourth, the concern that the ruling number 22-24/PUU-VI/2008 inhibit affirmative action policy has not been proven in Daerah Istimewa Yogyakarta (DIY), because the acquisition of women’s seats in parliament and city districts in Daerah Istimewa Yogyakarta (DIY) even more increased when compared to the acquisition in 2004 election.